Achieving sandwich-like laminated composite materials for robust superhydrophobicity, rapid photochromism and photo-mask writable media. (26th January 2022) - Zhang, Guofeng; Huang, Linqi; Yang, Fuchao
Abstract : Inspired by the superhydrophobicity of lotus leaves and the photochromic features of chameleons, the prepared PDMS@TKT possesses stable superhydrophobicity and fast-response reversible photochromic properties. Abstract : Photochromic materials with anti-water properties have impressive practical value, but their applications are severely hindered by their poor stability and slow colour-switching rate. Inspired by the superhydrophobicity of lotus leaves and the photochromic features of chameleons, herein we innovatively report a multifunctional material with stable superhydrophobicity and rapid photochromism. Initially, the extracted cellulose nanocrystals were utilized as the skeleton. After loading tungsten trioxide (TT) and Ketjen black (KB) on cellulose nanocrystals, the hybrid color-changing TT based sheet and composite conductive KB based sheet were constructed. Next, the TT sheet (upper layer and lower layer) and KB sheet (middle layer) were bonded with sodium carboxymethyl cellulose to prepare a sandwich-like laminated structure (denoted as TKT). Subsequently, TKT was modified by polydimethylsiloxane (PDMS) to prepare multifunctional PDMS@TKT. The PDMS ingredient can not only be used as an electron donor to increase the rate of discoloration but also endow PDMS@TKT with excellent waterproof performance. The superhydrophobicity of PDMS@TKT can withstand finger rubbing, temperature changes, acid–base corrosion, and UV radiation. PDMS@TKT can change its colour after 60 s of ultraviolet irradiation and then restore its original color after heating for 5 min, showing fast and highly reversible switching. Thus, PDMS@TKT has great potential for application in the fields of waterproof posters, light-driven sensors, and anti-counterfeiting security.